Persepsi Penggunaan Media Pembelajaran Wordwall dalam Pembelajaran bahasa Jerman kelas XI SMAN 15 Surabaya - Alisya, Zukhruf; Titaley, Audrey (LATERNE, 2025)
This research was based to explore students perceptions of using Wordwall learning media in German language learning in grade XI SMAN 15 Surabaya. This is based on the need to apply innovative use of interactive media in German language learning and to adapt to the characteristics of today’s students, who tend to actively use digital media in their daily lives. This research employed a descriptive quantitative method using a questionnaire for data collection, and the System Usability Scale (SUS) for data analysis. The research subjects were 30 eleventh-grade students. Based on the questionnaire results, it was found that 100% of respondents agreed that the Wordwall platform is easy to use. This statement was also supported by 93% of respondents who disagreed that they found the Wordwall platform difficult to use. The positive findings above align with the results of the SUS analysis: the average score was 79.58, classified as“acceptable high” with an “excellent” level of user satisfaction. Based on the research results, it could be concluded that students perceptions of the Wordwall platform were positive, so it can be recommended for use in German language learning at the high school level. However, students needed to be introduced of using the Wordwall platform first, as stated by 16.7% of respondents. Thus, students could use the Wordwall platform without difficulty and accept its use in learning.